“We try to give a good life to the children”-refugee parents and ECE professionals experiences of the early childhood education partnership in Norway - Lund, Hilde Hjertager (Frontiers in Education, 2024)
Introduction Children in Europe and Norway grow up in an increasingly culturally diverse society. As of 2022, 20% of children in Norwegian Early Childhood Education (ECE) institutions have a minority background. It is essential for parents and ECE professionals to work together to ensure a good start for these children. The partnership between the ECE institutions and parents is a statutory right and duty, and parents should, on equal terms, participate and influence what happens in the ECE institutions. However, research has shown a wide variation in how ECE professionals create partnerships with minority and refugee parents, and many find working with this group of parents challenging. This article explores the experiences of the interactions and encounters between refugee parents and ECE professionals in a Norwegian ECE setting. The aim is to analyze the tensions in this partnership and provide insights into these encounters, negotiation processes and their experiences. Methodology The study is based on semi-structured interviews with twelve refugee parents, interviews with six pedagogical leaders, and one kindergarten manager. Additionally, fieldwork was conducted in one ECE institution to provide contextual depth. Results The data is analyzed thematically using an inductive research design. Through this analysis, three prominent themes emerged: 1) Barriers, 2) “Norwegianness”, and 3) Trust. The findings highlight the importance of trust in children’s care and the ECE institution’s safety. At the same time, refugee parents emphasize education as a key to a promising future in Norway and value the education aspect of ECE institutions as high. Communication and language barriers pose an extra burden or stress for both ECE professionals and refugee parents. “Norwegianness” as a cultural norm within ECE institutions is linked to the values, norms, and cultural capital valid within the ECE institution. Discussion The findings are discussed within the theoretical frameworks of cultural capital and power relations and critical pedagogy. The interactions and encounters between refugee parents and ECE professionals show tensions arising from differences in cultural norms and understandings. In summary, this article explores the challenges posed by cultural diversity in ECE institutions and argues for using cultural sensitivity to foster more flexibility in these encounters to enhance inclusion and belonging in ECE institutions.